Determinants of consumers’ frugal innovation acceptance in a developed country - Costa, L.; Teixeira, A.; Brochado, A. (Young Consumers, 2021)
Purpose – This study aims to understand why young people are interested in buying frugal innovations. Design/methodology/approach – Data were collected with a survey administered to 534 university students enrolled in various fields of study (e.g. sciences, technology, economics and fine arts). Using the Tata Nano car as an example of frugal innovation, a model based on the unified theory of acceptance and use of technology was developed using partial least squares structural equation modeling. Findings – The model’s results reveal that effort expectancy, performance expectancy and facilitating conditions are critical factors that explain university students’ intention to buy Tata Nano. Originality/value – Although frugal innovations are often introduced first in developing countries, frugal innovations could be highly relevant to users in developed nations as these innovations can provide market opportunities in terms of cost-conscious, relatively low-income and sustainability-conscious consumers.